Photovoltaic cell aging test method

The surface of photovoltaic cells is coated, dried and aging by sodium ion solution, and the corrosion of sodium ions is accelerated, solving the problem of time-consuming and cost-effective testing methods of existing photovoltaic cells, achieving more efficient testing and evaluation.

CN119210342APending Publication Date: 2024-12-27TRINA SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411229727.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing photovoltaic cell aging testing methods require long-term and high-cost, and it is difficult to accurately evaluate the reliability of individual components, affecting the R&D cycle and market advancement.

Method used

The surface of the photovoltaic cell is coated with sodium ion solution. After drying and aging, sodium ions are used to accelerate the corrosion of the photovoltaic cell by water, shorten the test time and improve the test efficiency.

Benefits of technology

By accelerating the testing process and improving testing efficiency, reducing time costs, and improving the evaluation accuracy of the aging resistance and reliability of photovoltaic cells, it is suitable for many types of photovoltaic cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119210342A_ABST
    Figure CN119210342A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing aging of a photovoltaic cell. The method comprises the following steps: carrying out coating treatment on the surface of the photovoltaic cell by adopting a sodium ion solution; carrying out drying treatment on the photovoltaic cell subjected to the coating treatment; and carrying out aging treatment on the photovoltaic cell subjected to the drying treatment. According to the photovoltaic cell aging test method provided by the invention, the test process can be accelerated, the test time is shortened, and the test efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photovoltaic cell testing, and in particular, to a method for photovoltaic cell aging testing. Background Art

[0002] Photovoltaic cells are one of the key technologies for converting solar energy into electrical energy. However, photovoltaic cells face challenges from a variety of environmental factors in actual use, which may lead to performance degradation and reliability issues of photovoltaic cells. In order to ensure the long-term stability and efficiency of photovoltaic cells, aging tests are an important means to evaluate their aging resistance and reliability. By conducting aging tests, researchers and manufacturers can better understand the performance changes of photovoltaic cells under various environmental factors, so as to take corresponding design and material improvement measures to improve the reliability and service life of photovoltaic systems. With the continuous development of photovoltaic technology, the aging resistance and reliability evaluation methods of photovoltaic cells also need to be continuously innovated and improved to meet the growing energy demand and environmental challenges. Summary of the invention

[0003] In the first aspect of the present application, the present application proposes a method for testing aging of photovoltaic cells, comprising: coating the surface of the photovoltaic cell with a sodium ion solution; drying the photovoltaic cell after the coating; and aging the photovoltaic cell after the drying. Sodium ions can accelerate the corrosion effect of water on photovoltaic cells. By utilizing this feature, the method for testing aging of photovoltaic cells provided by the present application can speed up the testing process, shorten the testing time, and improve the testing efficiency.

[0004] In some embodiments, the solute of the sodium ion solution includes at least one of sodium chloride, sodium bicarbonate, and sodium carbonate. Thus, the cost of the sodium ion solution is low, and sodium ions can be provided in large quantities in a convenient manner.

[0005] In some embodiments, the concentration of the sodium ion solution is 0.06wt%-0.95wt%. Therefore, within the concentration range of the sodium ion solution, after the sodium ion solution is applied to the surface of the photovoltaic cell, the amount of sodium ions distributed per unit area is relatively appropriate.

[0006] In some embodiments, the coating process includes at least one of immersion, coating, and spraying, thereby allowing the sodium ion solution to be dispersed more evenly on the surface of the photovoltaic cell.

[0007] In some embodiments, the coating process includes coating the light-receiving surface and the backlight surface of the photovoltaic cell, thereby testing and evaluating the overall anti-aging performance of the photovoltaic cell.

[0008] In some embodiments, the coating process includes coating the light-receiving surface or the backlight surface of the photovoltaic cell, thereby evaluating the preparation process or anti-aging performance of the material on a certain side of the photovoltaic cell.

[0009] In some embodiments, the surface sodium ion concentration of the photovoltaic cell is 0.0005 mg / cm 2 -0.003mg / cm 2 The surface sodium ion concentration of the photovoltaic cell is within the aforementioned range, and the sodium ions can better promote the corrosion of the photovoltaic cell by water vapor.

[0010] In some embodiments, the drying temperature is 20° C.-28° C., and the drying time is 1 h-3 h. Thus, the water in the sodium ion solution can be fully dried.

[0011] In some embodiments, the temperature of the aging treatment is 50°C-95°C, the humidity of the aging treatment is 50RH%-95RH%, and the time of the aging treatment is 2h-10h. Therefore, under the aforementioned aging treatment conditions, it is sufficient to apply excessive environmental pressure to test the long-term reliability of photovoltaic cells.

[0012] In some embodiments, the method further comprises: performing a photoluminescence test and / or an electroluminescence test on the photovoltaic cell after the aging treatment, thereby testing the efficiency change of the photovoltaic cell.

[0013] In some embodiments, the photovoltaic cell includes at least one of a heterojunction cell, a multi-junction cell, a microcrystalline silicon cell, and a polycrystalline silicon cell. Therefore, the photovoltaic cell aging test method proposed in the present application can be applied to various types of photovoltaic cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0015] Figure 1 PL and EL test results of Example 1 of the present application;

[0016] Figure 2 PL and EL test results of Comparative Example 1 of this application;

[0017] Figure 3 PL and EL test results of Examples 2 to 6 of the present application;

[0018] Figure 4 PL and EL test results of Comparative Examples 2 to 6 of this application;

[0019] Figure 5PL and EL test results of Examples 7 to 11 of the present application;

[0020] Figure 6 These are the PL and EL test results of Comparative Examples 7 to 11 of the present application. DETAILED DESCRIPTION

[0021] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0022] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0023] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0024] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.

[0025] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0026] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0027] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0028] The damp heat test of photovoltaic cells is an important means to evaluate their performance and anti-aging properties in high temperature and high humidity environments, but the damp heat test requires the preparation of a large number of photovoltaic cells, and the testing cost is high. Moreover, conducting damp heat tests involves not only the cost of the cells themselves, but also the cost of test equipment and maintenance. In addition, damp heat tests usually require long exposure times to ensure the accuracy and reliability of the test results. This means that the test cycle may be as long as thousands of hours, which often leads to extended R&D cycles and delayed market launches, which is very unfavorable for the rapid iteration of products.

[0029] The wet heat test methods in the related art also have certain limitations. Specifically, because photovoltaic cells are composed of multiple components, including solar cells, packaging materials, backplanes, junction boxes, etc. The performance of these components in a wet and hot environment may affect each other, so that the test results cannot directly reflect the reliability of a component itself. The method of photovoltaic cell aging test proposed in this application can complete the test within a shorter test cycle, thereby reducing time costs. Furthermore, the performance of a certain side of the photovoltaic cell can be tested separately to reduce the influence of other components in the photovoltaic cell, thereby improving the accuracy of the test. By improving the testing technology, it is helpful to more effectively improve the evaluation of the aging resistance and reliability of photovoltaic cells, thereby helping to better and faster screen out photovoltaic cells that can operate stably for a long time under various environmental conditions, so as to adapt to the rapid development of the photovoltaic industry and increasingly stringent performance requirements.

[0030] In the first aspect of the present application, a method for testing aging of photovoltaic cells is proposed, comprising: coating the surface of the photovoltaic cell with a sodium ion solution; drying the photovoltaic cell after the coating treatment; and aging the photovoltaic cell after the drying treatment.

[0031] Sodium ions can accelerate the corrosion of photovoltaic cells by water. Based on the results of EL and PL tests, the Figure 1 and Figure 2 It can be seen that the efficiency attenuation of photovoltaic cells coated with sodium bicarbonate solution on the light-receiving side or the backlight side is much greater than that of photovoltaic cells coated with pure water. Specifically, Figure 1 In the figure, referring to the changes in the PL and EL graphs of the photovoltaic cell, it can be seen that the PL graph of the photovoltaic cell coated with sodium bicarbonate solution on the light-receiving side has no obvious change, but the local grid lines of the EL graph are black, indicating that the secondary grid of the photovoltaic cell has been corroded. The PL graph of the photovoltaic cell coated with sodium bicarbonate solution on the back side is obviously black, indicating that the passivation layer has been corroded, and the EL graph is completely black, indicating that the photovoltaic cell has been severely corroded. In contrast, Figure 2 In the figure, there is no obvious change in the PL and EL graphs of the photovoltaic cell coated with pure water. Therefore, it can be seen that Na ion corrosion accelerates the battery aging decay rate compared with pure water. Moreover, the decay of the backlight surface corrosion is significantly greater than that of the light-receiving surface, indicating that in addition to the corrosion caused by water vapor, Na ions also damage the backlight surface film layer of the photovoltaic cell, which can be used to evaluate the compactness of the photovoltaic cell film layer and its corrosion resistance to Na ions. Therefore, the method for photovoltaic cell aging test provided in this application can speed up the test process, shorten the test time, and improve the test efficiency.

[0032] In some embodiments, the solute of the sodium ion solution includes at least one of sodium chloride, sodium bicarbonate, and sodium carbonate. Thus, the aforementioned solute can provide sodium ions in the solution. Since the aforementioned solute has a high solubility, the sodium ion solution can be flexibly configured.

[0033] In some embodiments, the concentration of the sodium ion solution is 0.06wt%-0.95wt%. Within the concentration range of the sodium ion solution, after the sodium ion solution is applied to the surface of the photovoltaic cell, the amount of sodium ions distributed per unit area can better promote the corrosion of the photovoltaic cell by water vapor.

[0034] As an example, the concentration of the sodium ion solution may be 0.06wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt%, 0.55wt%, 0.6wt%, 0.65wt%, 0.7wt%, 0.75wt%, 0.8wt%, 0.85wt%, 0.9wt%, or 0.95wt%.

[0035] In some embodiments, the coating process includes at least one of immersion, coating, and spraying. Thus, the sodium ion solution can be dispersed more evenly on the surface of the photovoltaic cell, so as to perform an aging test with a relatively equal sodium ion concentration at various positions of the photovoltaic cell.

[0036] In some embodiments, the coating process includes coating the light-receiving surface and the backlight surface of the photovoltaic cell, thereby testing and evaluating the overall anti-aging performance of the photovoltaic cell.

[0037] In some embodiments, the coating process includes coating the light-receiving surface or the backlight surface of the photovoltaic cell, thereby evaluating the preparation process or anti-aging performance of the material on a certain side of the photovoltaic cell.

[0038] In some embodiments, the surface sodium ion concentration of the photovoltaic cell is 0.0005 mg / cm 2 -0.003mg / cm 2 .

[0039] As an example, the surface sodium ion concentration of the photovoltaic cell may be 0.0005 mg / cm 2 , 0.001mg / cm 2 , 0.0015mg / cm 2 , 0.002mg / cm 2 , 0.0025mg / cm 2 , 0.003mg / cm 2 .

[0040] refer to Figure 3-Figure 6, the same photovoltaic cell, coated with water and coated with sodium ion solution on the surface of the photovoltaic cell for aging test, comparing the PL map and EL map before and after the aging test, blackened areas appeared in the PL map and EL map after the aging test. Compared with the changes in the PL map and EL map before and after the aging test on the surface of the photovoltaic cell coated with water, the test results obtained by the aging test on the surface of the photovoltaic cell coated with sodium ion solution have more obvious aging contrast, indicating that the test efficiency is higher. Among them, the overall blackening of the EL map indicates that sodium ions have caused certain damage to the passivation layer of the photovoltaic cell. At the same time, the blackening near the grid line is more significant, indicating that sodium ions can accelerate the contact corrosion between the grid line and the photovoltaic cell. Therefore, within the surface sodium ion concentration range of the aforementioned photovoltaic cell, sodium ions can achieve better passivation layer destruction and contact corrosion acceleration.

[0041] In some embodiments, the drying temperature is 20°C-28°C, and the drying time is 1h-3h. Thus, the water in the sodium ion solution can be fully dried, and the retention of water in the sodium ion solution can be reduced, thereby reducing the humidity of the test conditions in the dry-burning aging treatment.

[0042] In some embodiments, the temperature of the aging treatment is 50°C-95°C, the humidity of the aging treatment is 50RH%-95RH%, and the time of the aging treatment is 2h-10h. Under the above aging treatment conditions, it is sufficient to apply excessive environmental pressure to achieve the purpose of testing the reliability and anti-aging performance of the photovoltaic cell.

[0043] As an example, the temperature of the aging treatment may be 50°C-95°C.

[0044] As an example, the humidity of the aging treatment may be 50RH%, 55RH%, 60RH%, 65RH%, 70RH%, 75RH%, 80RH%, 85RH%, 90RH%, 95RH%.

[0045] As an example, the aging treatment time may be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, or 10h.

[0046] In some embodiments, the method further comprises: performing a photoluminescence test and / or an electroluminescence test on the photovoltaic cell after the aging treatment. Thus, by observing the photoluminescence image or the electroluminescence image, the structure and defects of the photovoltaic cell after the aging test can be known, so as to understand the change in efficiency of the photovoltaic cell.

[0047] In some embodiments, the method further comprises: performing a photoluminescence test and / or an electroluminescence test on the photovoltaic cell before the aging treatment, thereby establishing a baseline of the structure and defects of the photovoltaic cell before the aging test for further analysis and comparison.

[0048] In some embodiments, the photovoltaic cell includes at least one of a heterojunction cell, a multijunction cell, a microcrystalline silicon cell, and a polycrystalline silicon cell. The photovoltaic cell aging test method proposed in the present application can be applied to various types of photovoltaic cells.

[0049] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0050] Example 1

[0051] Performing EL and PL tests on a photovoltaic cell, wherein the photovoltaic cell is a HJT photovoltaic cell;

[0052] Applying a 0.01 wt% sodium bicarbonate solution on the light-receiving side and the backlight side of the photovoltaic cell;

[0053] The photovoltaic cell was placed at 25°C for 2 hours to dry in the shade until there was no obvious watermark on the surface;

[0054] The photovoltaic cells after shade drying were placed in an environmental chamber with a temperature of 85°C and a humidity of 85 RH% for 2 hours.

[0055] The photovoltaic cells after aging test were subjected to EL and PL tests.

[0056] Example 2

[0057] Performing EL and PL tests on a photovoltaic cell, wherein the photovoltaic cell is a TOPCon photovoltaic cell;

[0058] Applying a 0.05 wt% sodium bicarbonate solution to the light-receiving surface of the photovoltaic cell;

[0059] The photovoltaic cell was placed at 25°C for 3 hours to dry in the shade until there was no obvious watermark on the surface;

[0060] The photovoltaic cells after shade drying were placed in an environmental chamber with a temperature of 85°C and a humidity of 85 RH% for 3 hours;

[0061] The photovoltaic cells after aging test were subjected to EL and PL tests.

[0062] Example 3

[0063] Example 3 is consistent with Example 2, except that the photovoltaic cell adopts a HJT cell, wherein TCO is formed by indium tin oxide (ITO)-pure silver paste.

[0064] Example 4

[0065] Example 4 is consistent with Example 3, except that the tin content of indium tin oxide is higher.

[0066] Example 5

[0067] Example 5 is consistent with Example 2, except that the photovoltaic cell adopts a HJT cell, wherein TCO is formed by indium tin oxide-silver coated copper slurry.

[0068] Example 6

[0069] Example 6 is consistent with Example 5, except that the tin content of indium tin oxide is higher.

[0070] Example 7

[0071] Performing EL and PL tests on a photovoltaic cell, wherein the photovoltaic cell is a TOPCon photovoltaic cell;

[0072] Applying a 0.05 wt% sodium bicarbonate solution on the backlight side of the photovoltaic cell;

[0073] The photovoltaic cell was placed at 25°C for 3 hours to dry in the shade until there was no obvious watermark on the surface;

[0074] The photovoltaic cells after shade drying were placed in an environmental chamber with a temperature of 85°C and a humidity of 85 RH% for 3 hours;

[0075] The photovoltaic cells after aging test were subjected to EL and PL tests.

[0076] Example 8

[0077] Example 8 is consistent with Example 7, except that the photovoltaic cell adopts a HJT cell, wherein TCO is formed by indium tin oxide-pure silver paste.

[0078] Example 9

[0079] Example 9 is consistent with Example 8, except that the tin content of indium tin oxide is higher.

[0080] Example 10

[0081] Example 10 is consistent with Example 7, except that the photovoltaic cell adopts a HJT cell, wherein TCO is formed by indium tin oxide-silver coated copper slurry.

[0082] Embodiment 11

[0083] Example 11 is consistent with Example 10, except that the tin content of indium tin oxide is higher.

[0084] Comparative Example 1

[0085] Comparative Example 1 is consistent with Example 1, except that pure water is used for coating.

[0086] Comparative Example 2

[0087] Comparative Example 2 is consistent with Example 2, except that pure water is used for coating.

[0088] Comparative Example 3

[0089] Comparative Example 3 is consistent with Example 3, except that pure water is used for coating.

[0090] Comparative Example 4

[0091] Comparative Example 4 is consistent with Example 4, except that pure water is used for coating.

[0092] Comparative Example 5

[0093] Comparative Example 5 is consistent with Example 5, except that pure water is used for coating.

[0094] Comparative Example 6

[0095] Comparative Example 6 is consistent with Example 6, except that pure water is used for coating.

[0096] Comparative Example 7

[0097] Comparative Example 7 is consistent with Example 7, except that pure water is used for coating.

[0098] Comparative Example 8

[0099] Comparative Example 8 is consistent with Example 8, except that pure water is used for coating.

[0100] Comparative Example 9

[0101] Comparative Example 9 is consistent with Example 9, except that pure water is used for coating.

[0102] Comparative Example 10

[0103] Comparative Example 10 is consistent with Example 10, except that pure water is used for coating.

[0104] Comparative Example 11

[0105] Comparative Example 11 is consistent with Example 11, except that pure water is used for coating. Test method:

[0106] EL test (Electro-Luminescence), reference standard IEC TS 60904-13. PL test (Photo-Luminescence), reference standard T / CPIA 0020—2020. Test results:

[0107] The test results of Example 1 and Comparative Example 1 are shown in Table 1;

[0108] The test results of Examples 2-6 and Comparative Examples 2-6 are shown in Table 2;

[0109] The test results of Examples 7-11 and Comparative Examples 7-11 are shown in Table 3.

[0110] Table 1

[0111]

[0112] Table 2

[0113]

[0114]

[0115] Table 3

[0116]

[0117] Table 2 and Table 3 are the test results of the efficiency changes of the light-receiving side and the backlight side of the photovoltaic cell before and after the aging test. Figure 3 and Figure 4 ,contrast Figure 5 and Figure 6 It can be seen that for the same light-receiving and back-lighting surfaces of photovoltaic cells, the efficiency changes of the water-coated test are smaller than those of the sodium ion solution-coated test. Sodium ions are corrosive to both the light-receiving and back-lighting surfaces of photovoltaic cells. Figure 3 and Figure 5 It can be seen that for the same photovoltaic cell, the efficiency change is greater when the sodium ion solution is applied on the backlight side than when it is applied on the light-receiving side. Both the PL and EL graphs show more blackened areas, indicating that the sodium ion solution coating has a more obvious corrosion effect on the backlight side of the photovoltaic cell. In both cases of coating with water and coating with sodium ion solution, the efficiency change of TOPCon cells is smaller than that of HJT cells, indicating that TOPCon cells have better aging resistance and reliability. Among them, reference Figure 5 , a large area of ​​the PL image of the backlight side of the HJT battery turned black, and the EL image turned black, indicating that Na ions have the ability to penetrate the passivation layer on the backlight side.

[0118] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0119] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all the steps of the present application can be carried out in sequence or randomly, preferably in sequence. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) carried out in sequence, or may include steps (b) and (a) carried out in sequence. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc. It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and playing the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. Furthermore, other embodiments in which various modifications that can be conceived by those skilled in the art are added to the embodiments and some components of the embodiments are combined to form other embodiments are also included in the scope of the present application without departing from the gist of the present application.

Claims

1. A method for testing aging of photovoltaic cells, characterized in that: include: Using a sodium ion solution to coat the surface of the photovoltaic cell; Drying the photovoltaic cell after the coating process; The photovoltaic cell after the drying process is subjected to an aging process.

2. The method according to claim 1, characterized in that The solute of the sodium ion solution includes at least one of sodium chloride, sodium bicarbonate and sodium carbonate.

3. The method according to claim 2, characterized in that The concentration of the sodium ion solution is 0.06wt%-0.95wt%.

4. The method according to claim 1, characterized in that: The coating process includes at least one of dipping, coating, and spraying.

5. The method according to any one of claims 1 to 4, characterized in that: The coating process includes performing the coating process on the light-receiving surface and the backlight surface of the photovoltaic cell.

6. The method according to any one of claims 1 to 4, characterized in that: The surface sodium ion concentration of the photovoltaic cell is 0.0005 mg / cm 2 -0.003mg / cm 2 .

7. The method according to any one of claims 1 to 4, characterized in that: The temperature of the drying treatment is 20° C.-28° C., and the time of the drying treatment is 1 h-3 h.

8. The method according to any one of claims 1 to 4, characterized in that: The temperature of the aging treatment is 50° C.-95° C., the humidity of the aging treatment is 50RH%-95RH%, and the time of the aging treatment is 2h-10h.

9. The method according to claim 1, characterized in that: Further including: The photovoltaic cell after the aging treatment is subjected to a photoluminescence test and / or an electroluminescence test.

10. The method according to claim 1, characterized in that The photovoltaic cell includes at least one of a heterojunction cell, a multi-junction cell, a microcrystalline silicon cell, and a polycrystalline silicon cell.